Area-efficient and low stand-by power 1k-byte transmission-gate-based non-imprinting high-speed erase (TNIHE) SRAM - Ho, Weng-Geng (2016)
We propose a novel 15-T Transmission-gate-based Non-Imprinting High-speed Erase (TNIHE) SRAM cell with emphases on low area overhead and low stand-by power attributes for highly secured data storage applications. We benchmark our proposed 15-T TNIHE SRAM cell against the reported 22-T Non-Imprinting High-speed Erase (NIHE) SRAM cell, and demonstrated three key features of reducing 7 transistors. First, we adopt the transmission gates (as opposed the cross-couple inverters) in the slave circuitry, saving 4 transistors. Second, we eliminate a transistor which uses to reset the slave circuitry, hence saving 1 transistor. Third, we apply the global inverse transistors (as opposed to the local inverse transistors) in the read /write circuit for each SRAM cell, hence further reduce 2 more transistors. As a result, our proposed TNIHE SRAM cell @ 65nm CMOS features ~17% smaller layout area. We design a 1k-byte memory based on the proposed TNIHE SRAM cells. On the basis of simulations, we show that our 1k-byte SRAM memory features overall ~13% smaller area, and dissipates on average, ~30% lower stand-by power than the reported NIHE counterpart.